Parallel computing technologies : 13th International Conference, PaCT 2015, Petrozavodsk, Russia, August 31-September 4, 2015, Proceedings /: 13th International Conference, PaCT 2015, Petrozavodsk, Russia, August 31-September 4, 2015, Proceedings. (2015) - Unknown
No abstract available